Time trial performance in normal and high ambient temperature: is there a role for 5-HT? - Roelands, B.; Goekint, M.; Buyse, L.; Pauwels, F.; de Schutter, G.; Piacentini, F.; Hasegawa, H.; Watson, P.; Meeusen, R. (European Journal of Applied Physiology, 2009)
The original central fatigue hypothesis suggested that fatigue during prolonged exercise might be due to higher 5-HT activity. Therefore, we examined the effects of acute administration of a selective 5-HT reuptake inhibitor (SSRI) on performance and thermoregulation. Eleven healthy trained male cyclists completed four experimental trials (two in 18°C, two in 30°C) in a double-blind randomised crossover design. Subjects ingested either a placebo (PLA: lactose 2 × 10 mg) or citalopram (CITAL 2 × 10 mg) on the evening before and the morning of the trial. Subjects cycled for 60 min at 55% W max, immediately followed by a time trial (TT) to measure performance. The significance level was set at P < 0.05. Acute SSRI did not significantly change performance on the TT (18°C P = 0.518; 30°C P = 0.112). During recovery at 30°C, core temperature was significantly lower in the CITAL trial (P < 0.012). At 30°C heart rate was significantly lower after exercise in CITAL (P = 0.013). CITAL significantly increased cortisol concentrations at rest (P = 0.016), after the TT (P = 0.006) and after 15-min recovery (P = 0.041) at 30°C. 5-HT reuptake inhibition did not cause significant reductions in performance. Core temperature was significantly lower only after the time trial in heat after CITAL administration. The present work failed to prove whether or not 5-HT has an exclusive role in the onset of centrally mediated fatigue during prolonged exercise in both normal and high ambient temperature.